2020
DOI: 10.1126/sciadv.aaz5913
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial screening of biochemical and physical signals for phenotypic regulation of stem cell–based cartilage tissue engineering

Abstract: Despite great progress in biomaterial design strategies for replacing damaged articular cartilage, prevention of stem cell-derived chondrocyte hypertrophy and resulting inferior tissue formation is still a critical challenge. Here, by using engineered biomaterials and a high-throughput system for screening of combinatorial cues in cartilage microenvironments, we demonstrate that biomaterial cross-linking density that regulates matrix degradation and stiffness—together with defined presentation of growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Immunofluorescence staining of Sox9 showed that the 10–20% D/S group had higher expression than the 30% D/S group ( Appendix A , Appendix A ). These results suggested that 30% D/S group with excessive stiffness and smooth surface is unsuitable for chondrocyte growth and chondrogenesis [ 35 , 36 ]. On the other hand, almost all BMSCs were alive on the P/S materials, verifying the excellent biocompatibility of this scaffold ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence staining of Sox9 showed that the 10–20% D/S group had higher expression than the 30% D/S group ( Appendix A , Appendix A ). These results suggested that 30% D/S group with excessive stiffness and smooth surface is unsuitable for chondrocyte growth and chondrogenesis [ 35 , 36 ]. On the other hand, almost all BMSCs were alive on the P/S materials, verifying the excellent biocompatibility of this scaffold ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent studies exploring the relationship between biomechanical properties and hypertrophy in cell culture models have already been published. 50,51 These studies, however, were not performed with a hypertrophic model based on spheroids to understand how the biomechanical properties of hypertrophic induced spheroids can influence their buildingblock capacity for bioassembly approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) signaling are important in the development of cartilage ( Vanyai et al, 2020 ). Specifically, low level of yes-associated protein (YAP), a transcription factor of the Hippo pathway, was associated with the formation of articular cartilage from MSCs ( Lee et al, 2020 ). Using murine models, Deng et al demonstrated that Yap1 overexpression significantly reduced COL10A1 level, which however was at the expense of reduced chondrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mechanical loading, under certain conditions, was shown to suppress hypertrophy ( Aisenbrey et al, 2019 ). In the study by Lee et al, MSCs cultured in 3D chondrogenic combinatorial system with 40% strain showed a trend toward hypertrophic chondrocytes, indicated by the high level of RUNX2, which was also accompanied with more YAP expression ( Lee et al, 2020 ). Of note, the association between mechanical loading and Wnt/β-catenin has been previously demonstrated ( Sen et al, 2011 ; He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%